Eksperimental Kekerasan Dan Struktur Mikro Pada Produk Foot Step Berbahan Limbah Alumunium Hasil Pengecoran Cetakan Pasir Silika Berpengikat Bentonit - S, Dendi; Siregar, Ahmad Marabdi; Siregar, Chandra Amirsyah Putra; Nasution, Arya Rudi; Mahjudin, Mahyunirsyah (Fakultas Teknik UMSU, 2022)
This study aims to determine the results of the hardness values of castings using silica sand molds on market products and the microstructure contained in the results of various mold castings. Aluminum is often used as a material for making automotive components, machinery, art objects, and household appliances. Aluminum is a lightweight metal that is corrosion resistant. The foundry industry has now developed a lot from metal casting to non-metal casting. One of the metal casting technologies known today is metal casting technology with sand casting, the casting carried out in this study uses sand molds. The materials used in this study include silica sand, bentonite, water, aluminum waste, and the tools used include patterns, melting furnaces, scales, sand paper. In this research, testing, hardness test and microstructure test were carried out. The results of the hardness test on the standard specimen have an average value of 76.33 BHN, the first mold variation specimen has an average value of 63.69 BHN, and the second mold variation specimen has an average value of 63.84 BHN. In the microstructure test, the first variation of the castings had good aluminum dispersion, a high level of porosity, and for the second variation specimen the castings had good aluminum dispersion and low porosity. After seeing the results of the hardness and microstructure tests, it can be explained that the market product has a better value for the test results, this is because the results of the castings use permanent molds, and it can also be seen that the results of the microstructure affect a hardness value of the two results of the bentonite-binding silica sand mold castings.